Role of postoperative lubrication in preventing dry eye after cataract surgery in high- and low-risk patients stratified by ocular surface frailty index - Stefan Palkovits; Andreas Schlatter; Manuel Ruiss; Andreea Fisus; Natascha Bayer; Paul Kofler; Oliver Findl (PLoS ONE, 2025)
Purpose Symptoms and signs of dry eye can significantly increase after cataract surgery. The present study seeks to investigate the effect of intensive lubrication using Systane HYDRATION multi-dose preservative free (MDPF) eye drops (Alcon Research, Ltd., Fort Worth, Texas, USA) on signs and symptoms of dry eye in the postoperative phase. Methods Patients scheduled for cataract surgery were enrolled in this randomised, investigator-masked study and assigned to one of three groups. The risk of developing dry eye was stratified using the ocular surface frailty index (OSFI). The high risk – standard of care (HR-SOC) and treatment (HR-Treatment) group were the high-risk groups (OSFI 0.3 or greater), and the LR-SOC group was the low-risk group (OSFI less than 0.3). HR-SOC and LR-SOC group received the standard postoperative treatment. In the HR-Treatment group, Systane HYDRATION MDPF was added four times a day for three months after surgery. After the baseline examination prior to cataract surgery, three follow up visits were scheduled one week, one month and three months after surgery. OSDI scores, ocular surface staining, and fluorescein break-up time were assessed at each visit. Results Ninety-five patients were included and 83 entered statistical analyses. OSDI increased in all groups after cataract surgery, and it was lowest in the HR-Treatment group three months after the surgery. In addition, fluorescein break-up time tended to be longer and ocular surface staining less in the HR treatment group at three months. However, there was no statistically significant difference between the groups during the three-month visit. Conclusion In this randomized, examiner-masked trial no statistically significant difference could be found between the groups, but Systane HYDRATION MDPF may have a positive effect after cataract surgery in high-risk groups for dry eye syndrome. Trial registration ClinicalTrials.gov NCT06555224